(untitled) (Bangladesh Journal of Public Administration, 2022)
The purpose of this study is to investigate the impact of green human resource management practices on organizational citizenship behaviour towards the environment based on the Ability-Motivation-Opportunity (AMO) theory. To support statistical analyses, relevant data were gathered from 132 employees working in the commercial banking sector of Bangladesh. To assess the research model, the PLS-SEM approach was applied using SmartPLS 3.0. The study found a significant positive impact of green training and development, green performance appraisal, and green employee empowerment on organizational citizenship behaviour towards the environment. Besides, deviated from previous studies, we found green recruitment and selection, and green rewards were not significant predictors to employee green behaviour. The results of the study suggest that organizations should provide more attention to green employee empowerment, and green training and development to develop responsible eco-friendly behaviour among the participants. Moreover, the study suggests some new research perspectives considering organizational and individual variables to get more insights on the issue and to overcome the limitations of this research.